2022
DOI: 10.3390/vaccines10050646
|View full text |Cite
|
Sign up to set email alerts
|

Cost per Responder Analysis of Secukinumab versus Adalimumab in the Treatment of Psoriatic Disease

Abstract: Background: The EXCEED study evaluated the efficacy and safety of secukinumab versus adalimumab in psoriatic arthritis, but it did not include a pharmacoeconomic analysis. The objective of this study was to compare the cost per responder of secukinumab versus adalimumab in patients with psoriatic disease. Methods: The cost per responder was calculated by multiplying the cost of treatment by the number needed to treat for each therapy. The 52-week primary endpoint was the American College of Rheumatology respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…The treatment of moderate-to-severe psoriasis with biologic agents poses a significant economic burden to healthcare systems [ 6 , 12 , 13 , 44 ]. Despite increasing recognition of the potential of biologic therapies to reduce both direct and indirect healthcare costs in the long term, economic considerations focusing solely on drug acquisition costs mean that they often remain restricted to patients with only the most severe forms of disease.…”
Section: Unmet Medical Needs and Potential Role Of Biosimilarsmentioning
confidence: 99%
See 1 more Smart Citation
“…The treatment of moderate-to-severe psoriasis with biologic agents poses a significant economic burden to healthcare systems [ 6 , 12 , 13 , 44 ]. Despite increasing recognition of the potential of biologic therapies to reduce both direct and indirect healthcare costs in the long term, economic considerations focusing solely on drug acquisition costs mean that they often remain restricted to patients with only the most severe forms of disease.…”
Section: Unmet Medical Needs and Potential Role Of Biosimilarsmentioning
confidence: 99%
“…Recently, biosimilars have provided a more cost-effective alternative to off-patent biologic therapies within IMIDs, including psoriasis [ 10 , 11 ]. In particular, evidence is mounting to confirm the use of biosimilars as a valuable pharmacoeconomic strategy to lower healthcare cost in patients with psoriasis [ 6 , 12 , 13 ], thereby allowing the use of biologics by a wider group of patients and earlier in the disease course.…”
Section: Introductionmentioning
confidence: 99%
“…Both genetic and environmental factors play a relevant role in psoriasis pathogenesis. Most psoriasis susceptibility loci are related to inflammatory and immunity genes [ 4 , 5 , 6 ]. Environmental and triggering factors include infections (including COVID), stressful life events, medications, skin trauma, and air pollution [ 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Most psoriasis susceptibility loci are related to inflammatory and immunity genes [ 4 , 5 , 6 ]. Environmental and triggering factors include infections (including COVID), stressful life events, medications, skin trauma, and air pollution [ 4 , 5 , 6 ]. Early events in the development of psoriasis lesions include the recruitment and the activation of plasmacytoid dendritic, which together with natural killer cells and macrophages, secrete cytokines such as IFN-γ, IL-1β, and TNF-α.…”
Section: Introductionmentioning
confidence: 99%
“…Among the chronic diseases with the highest prevalence, rheumatological diseases are to be counted. Specifically, arthritis is diagnosed in 23% of adult Americans and psoriasis affect 1–4% of the population worldwide [ 6 , 7 ]. Additionally, a recent report by the World Health Organization (WHO), has revealed that infectious diseases, specifically lower respiratory infections, represent the first cause of communicable death worldwide, for both males and females [ 8 ].…”
mentioning
confidence: 99%